Ionic liquid-based dispersive liquid–liquid microextraction followed by dispersive solid phase extraction coupled with HPLC-DAD for the determination of sulfonylurea herbicides in soymilk samples. Issue 13 (9th August 2021) - Li, Jilong; Xu, Weili; Wang, Xiujuan; Wu, Fengze; Wang, Lin; Feng, Ji; Wang, Zhibing; Zhang, Hanqi
Abstract: The ionic liquid-based dispersive liquid-liquid microextraction followed by dispersive solid phase extraction (IL-DLLME-DSPE) was developed and applied to the extraction of six sulfonylurea herbicides in soymilk samples. High performance liquid chromatography coupled with a diode-array detector was used for the separation and determination of analytes. In this study, [P4 4 4 12 ] [BF4 ] was used as an extraction solvent in DLLME and montmorillonite K10 was used as an adsorbent in DSPE. After DLLME and DSPE, the ionic liquid and analytes were adsorbed by montmorillonite K10 and separated from the sample solution. Subsequently, the analytes were desorbed from montmorillonite K10 by acetonitrile. Some parameters, including type and amount of ionic liquid, pH of sample solution, centrifugal speed, and amount of montmorillonite K10, were investigated and optimized. The limits of detection and quantification for analytes were in the range of 1.53–2.32 and 5.10–7.73 µg L −1, respectively. The relative standard deviations for intra-day and inter-day precision were in the range of 1.12–3.59 and 1.99–6.48%, respectively. When the present method was applied to the analysis of real soymilk samples, the recoveries of the analytes were 81.95–118.95%. The results showed that the present method is effective for the extraction of the sulfonylurea herbicides in soymilk samples. Graphical Abstract: UF0001